Pengaruh Self-Compassion terhadap Resilience at Work Guru Sekolah Menengah Atas (SMA) - Nadya Tridamayanti; Dinda Dwarawati (Bandung Conference Series: Psychology Science, 2023)
Abstract. Self-Compassion is an intrapersonal process of understanding pain and understanding that struggle is part of the human experience (Neff, 2003a, 2003b). Self-compassion according to Neff and Germer (2017) will make individuals feel able to develop competencies, and make a greater effort to maintain higher persistence towards goals even when faced with difficulties, therefore according to Lewis and Ebbeck (2014) the element of self-compassion increases positive outcomes and makes individuals more resilient at work (resilience at work). This study aims to determine how much influence Self-Compassion has on Resilience at Work. This research was conducted on high school teachers (SMA) in the city of Bandung with a subject of 157 teachers. This study uses a scale with the Resilience at Work measuring instrument from Malik and Garg (2018) which was adapted by the researcher, and the Self-Compassion Scale from Neff (2003) which was adapted by Sugianto, Christiany, and Sandra (2020). The results showed that 88.5% of teachers had high Resilience at Work and 90.4% of teachers had high Self-Compassion. The effect of Self-Compassion on Resilience at Work in this study was 41.8%. The data analysis technique uses Simple Linear Regression. The results of the research show that there is a positive relationship where for every addition of 1% Self-Compassion, the Resilience at Work on the teacher increases by 0.603. Abstrak. Self-Compassion adalah suatu proses intrapersonal untuk memahami rasa sakit dan memahami bahwa perjuangan termasuk bagian dari pengalaman manusia (Neff, 2003a, 2003b). Self-compassion menurut Neff dan Germer (2017) akan membuat individu merasa mampu mengembangkan kompetensi ,dan melakukan usaha yang lebih besar untuk mempertahankan kegigihan yang lebih tinggi terhadap tujuan bahkan ketika dihadapkan dengan kesulitan, oleh karena itu menurut Lewis dan Ebbeck (2014) elemen self-compassion meningkatkan hasil positif dan membuat individu lebih memiliki resiliensi pada pekerjaanya (resilience at work) . Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh Self-Compassion terhadap Resilience at Work. Penelitian ini dilakukan pada Guru Sekolah Menengah Atas (SMA) di Kota Bandung dengan subjek sebanyak 157 guru. Penelitian ini menggunakan skala dengan alat ukur Resilience at Work dari Malik dan Garg (2018) yang diadaptasi oleh peneliti, dan alat ukur Skala Self-Compassion dari Neff (2003) yang diadaptasi oleh Sugianto, Christiany, dan Sandra (2020). Hasil penelitian menunjukan 88.5% guru memiliki Resilience at Work yang tinggi dan 90.4% guru memiliki Self-Compassion yang tinggi. Pengaruh Self-Compassion terhadap Resilience at Work pada penelitian ini sebesar 41.8%. Teknik analisis data menggunakan Regresi Linier Sederhana. Hasil penelitain menunjukan bahwa terdapat hubungan yang postif dimana setiap penambahan 1% Self-Compassion maka Resilience at Work pada guru meningkat 0.603.